Theoretical notes about Lima’s archaelogical prehispanic heritage. The Garagay case - Becerril Cotera, Eduardo Martín (2022)
Lima is a city where the area of archaeological sites exceeds the green and public areas, this represents an enormous challenge to preserve and reclaim our monuments, so it’s necessary to evaluate the theory with which we face this challenge; This Research reviews conceptual presents a literatura review based in different contributions on the pre-Hispanic territorial model and its evolution over time, it also seeks to contrast the approaches of value enhancement and social use to assess its relevance to the contemporary context of archaeological sites in Lima, its relevance for the city and their value enhancement process, and finally, it analyzes the case of urban dynamics in Garagay to understand its relevance in the urban environment and related concepts of enhancement.